2023
DOI: 10.1093/jleuko/qiad004
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-activated neutrophils promote metastasis in breast cancer via the G-CSF-RLN2-MMP-9 axis

Abstract: The immune component of the tumor microenvironment is essential for the regulation of cancer progression. In breast cancer (BC), a patient’s tumor mass is frequently infiltrated by neutrophils (tumor-associated neutrophils, TANs). Our study addressed the role of TANs and their mechanism of action in BC. Using quantitative IHC, ROC, and Cox analysis, we demonstrated that a high density of TANs infiltrating the tumor parenchyma was predictive of poor prognosis and of decreased progression-free survival of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…The results of our work suggest that increased CD66b+ cell density both in the stromal and intraepithelial compartment of central tumor tissue from early luminal breast cancers is a negative predictive factor associated with tumor progression. This is consistent with the above-mentioned results of studies in other subtypes of breast cancer [27,28,30,31]. In addition, we also made intriguing novel observations in tissue beyond the primary tumor: Although there was limited availability of normal tissue samples in this study, a negative prognostic relevance of CD66b+ cells was also observed in these samples.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of our work suggest that increased CD66b+ cell density both in the stromal and intraepithelial compartment of central tumor tissue from early luminal breast cancers is a negative predictive factor associated with tumor progression. This is consistent with the above-mentioned results of studies in other subtypes of breast cancer [27,28,30,31]. In addition, we also made intriguing novel observations in tissue beyond the primary tumor: Although there was limited availability of normal tissue samples in this study, a negative prognostic relevance of CD66b+ cells was also observed in these samples.…”
Section: Discussionsupporting
confidence: 91%
“…In hepatocellular cancer, Zhou et al reported the recruitment of tumor-associated macrophages by TANs as a mechanism of tumor progression [36]. Tumor-induced G-CSF release, which as described by Sheng et al promotes metastasis in TANs via the G-CSF-RLN2-MMP-9 axis, also affects the polarization of TAMs to the immunosuppressive M2-like phenotype [31].…”
Section: Discussionmentioning
confidence: 99%
“…N2 neutrophils are characterized by overexpression of VEGF and CXCR4, promoting tumor proliferation by facilitating tumor angiogenesis, invasion, and metastasis (21) . Both M2 macrophages and N2 neutrophils have been reported to exhibit negative predictive value for patient survival outcomes (22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that immune cells infiltrating tumors can be influenced by interactions in the tumor microenvironment to support tumor progression (Kwantwi 2023b , 2023c ; Sheng et al 2023 ; Peng et al 2021 ; Cai et al 2020 ; Kwantwi et al 2021a ; Li et al 2021 ). Notably, autophagy induction can shape immune cells to gain protumor functions leading to therapeutic resistance and tumor progression (Bustos et al 2020 ; Ishimwe et al 2020 ; Jiang et al 2019 ; Janji et al 2018 ).…”
Section: The Tumor Microenvironment Promotes Drug Resistance Through ...mentioning
confidence: 99%